THE IMAGE OF NATURE IN THE WORK OF A.S. PUSHKIN (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The great Russian poet, Alexander Sergeevich Pushkin, in his work not only sang human passions, but also elevated nature to an image with its own life and meaning. The theme of nature was most often expressed in the description of landscapes. The writer masterfully approached the depiction of the water element, forest sketches, mountain landscapes and the endless distance of the sky.